Comparative study of three different bridge-less converters for reduction of harmonic distortion in brushless DC motor - Santanu Mondal; Madhurima Chattopadhyay (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
This paper represents a comparative study of three different types of DC-DC converter that can be used for reduction of total harmonic distortion (THD) in stator current, back electromotive force (EMF) and torque of brush less DC motor. In addition, the topologies of these converters are analysed, and the THD of the output characteristics have also been studied. In this work, SEPIC, Zeta and Flyback converters are considered and their outputs are fed to the BLDCM with the help of universal bridge or six step inverter. Moreover the THD of the output voltages are not only measured for three converters but also reduced by tuning the parameters. At first these three converters are modeled in MATLAB/ Simulink based simulation platform and studied the performance individually and further executed with hardware circuitry. Finally the output parameters from both software simulation and real time hardware are compared for these three converters separately and got satisfactory similar results. Again we studied the performance with these converters in terms of efficiency while fed in the commutation drive circuitry of BLDCM by considering minimum THD. From this comparative simulation results, it has been observed that Zeta converter showed maximum efficiency. Therefore, in real time hardware implementation, the commutation drive circuitry of BLDCM is studied with Zeta converter. With this configuration, a comparatively low THD of stator current, back EMF and electromagnetic torque have been achieved in BLDCM with PID controller.